Perkembangan Persatuan Ummat Islam (PUI) di Cianjur Tahun 1935-2014 - Afifatul, Asmi; Sulaiman, Asep (Historia Madania: Jurnal Ilmu Sejarah, 2019)
PUI is a fusion (combined) organization of two other organizations, namely the Islamic Community Engagement of Majalengka led by KH Abdul Halim and the Indonesian Islamic Community Association (PUII) of Sukabumi led by KH Ahmad Sanusi. In this research, the writer focuses on PUI Cianjur regency because Cianjur has a fairly long history with this organization and Cianjur has also become one of the PUI branches that has the most members. To find out the problems in this study, there are several points that will be explained, namely the social and religious conditions of the people of Cianjur district and the development of PUI in Cianjur starting from 1935-2014. To be able to understand the problems in this study, the writer uses institutional social theory. The method used in this research is the historical research method, while the steps of the research are, heuristics (search and collection of sources), criticism (external and internal), interpretation (interpretation), and historiography. The results of this study can be said that over time PUI in Cianjur experienced ups and downs in running the wheels of its organization, caused by factors that influence it. Both internal and external factors. The social and religious conditions of the Cianjur community at that time were able to accept PUI well, because PUI came with good Islamic teachings and good ways. So that in a fairly long span of time PUI Cianjur experienced a vacuum, a transition period and a revival or development period. Especially in 2008 until 2014, even now. PUI is still alive and well known in the community.